PENGARUH PENAMBAHAN SILIKA FUME TERHADAP KUAT TEKAN BETON - A, Arman; Mulyati, Mulyati; Nugroho, Fajar; Fakhrizal, Fakhrizal; Fadhil Azman, Hanif (ITP Press, 2024)
The development of technology in Indonesia is currently experiencing a fairly rapid development, especially in the construction sector. Concrete is one of the construction materials that is often used in various types of construction such as buildings, bridges, roads, dams and other civil infrastructure. Concrete consists of a mixture of coarse aggregate, fine aggregate, cement, water and sometimes concrete can also be added with chemicals and non-chemicals in certain ratios. Therefore, this study aims to determine the effect of the addition of Silica fume on the compressive strength of concrete. In this study using Silica fume with percentages of 0%, 4%, 7%, and 10% of the cement weight with 1 sample for each percentage. Examination of the physical properties of the concrete material is carried out in the Civil Engineering laboratory of ITP and testing of the compressive strength of concrete is carried out in the laboratory of the Department of Public Works. This research uses the standard material of SNI 7656-2012. The test object used is a steel cylinder with a diameter of 150 mm x a height of 300 mm. Based on the results of the compressive strength test of concrete carried out at the Department of Public Works laboratory at the age of 28 days from normal concrete, the compressive strength value was 27.03 MPa, concrete with the addition of 4% Silica fume experienced an increase in compressive strength of 1.59% with the obtained value The compressive strength is 27.46 MPa, the concrete with the addition of 7% Silica fume has decreased the compressive strength by 8.38% with the obtained compressive strength value of 24.76 Mpa, and the concrete with the addition of 10% Silica fume has decreased the compressive strength by 26.89% with the obtained compressive strength value of 19.76 Mpa. From this data it is known that the optimum compressive strength value is obtained with the addition of 4% Silica fume, which is 27.46 Mpa. After conducting this research, it can be concluded that the addition of Silica fume to the mixture for making concrete can be carried out with the provisions for the addition of Silica Fume below 4% of the weight of cement.